(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study assessed vaccine acceptance, hesitancy, and skepticism among adults aged 18 years and above in Hyderabad, India, amid the COVID-19 pandemic. Conducted from November 2020 to June 2021, the web-based observational survey gathered responses from 255 participants using a comprehensive questionnaire. The survey examined socio-demographic aspects, understanding of COVID-19 and vaccinations, perceptions of vaccine safety and effectiveness, and readiness to financially contribute to receiving the vaccine. The findings revealed that 84.71% 84.71% of the individuals were open to getting the COVID-19 vaccination, while 26.67% identified as anti-vaxxers. The majority of respondents (88.63%) concurred that vaccines are crucial in preventing severe illnesses. However, 58.43% expressed worries about potential long-term health issues arising from the vaccine. Trust in vaccine producers was mixed, with 61.96% expressing trust. Education level significantly influenced vaccine acceptance, with higher-educated individuals showing greater willingness to get vaccinated. These insights into vaccine acceptance and perceptions offer valuable guidance for policymakers and authorities responsible for public health in dealing with vaccine reluctance and improving vaccination campaigns. The findings of the study are crucial in the current context of increasing reports of adverse vaccine effects, providing valuable guidance for public health strategies to enhance vaccine uptake.